Personal data in the process of commercializing the results of scientific activities - Rutkowska-Sowa, Magdalena; Siemion , Katarzyna (Prawo Kanoniczne, 2024)
The process of commercializing scientific research results involves extensive processing of personal data of creators, research participants, and business partners. The article analyzes the obligations of universities under the GDPR, in particular those relating to establishing the legal basis for processing, data minimization, pseudonymization, and ensuring information security. It also presents the role of universities as controllers, processors, or joint controllers, and the obligations associated with each of these roles. The authors draw attention to the need to take data protection principles into account in the design of new technologies and services (privacy by design and by default), as well as to the growing importance of appropriate procedures, training, data protection officer supervision, and technical measures. It is emphasized that compliance with the GDPR is not only a legal obligation, but also an element that builds trust among partners and increases the competitiveness of universities in the area of research and technology transfer.